Is the united intelligence response, the end of speciesism and the emergence of new avatarism? - Silva, Susana C. (2022)
With the advancements in artificial intelligence (AI) research, the "algorithm aversion" concept has become evident, referring to situations in which an algorithm consistently beats human judgment, despite people's preference for interaction with humans. Moreover, another idea following this one emerged: the concept of "uncanny valley" referring to people feeling comfortable dealing with AI for solving more cognitive-oriented tasks and less prone to condescend to, share feelings with, and feel less proximity to it, for more emotional experiences. Despite this visible aversion but apparent reliability in AI mechanisms, the truth is that AI seems to be inescapable in different fields, inclusively in the interaction with the public. Thus, it is probably time to ask ourselves if living along with these forms of intelligence is not inevitable, with full respect for each other's idiosyncrasies. And, if it is not about time either to start foreseeing the world as a place where a united intelligence response would eventually emerge and give space for a new avatarism era. This manuscript aims to start immersing in this quest.